Experimental laboratory and problem solving: building chemical knowledge (Research, Society and Development, 2020)
This work develops an approach that involves aspects of interactions between teachers, students and the researcher, in the classroom and laboratory of Natural Sciences. It aims to bring relevant contributions to the teaching and learning of chemistry, as well as working with experimentation and problem solving in basic education. The research was implemented in three schools in greater Porto Alegre, RS and covered 5 classes of the 1st year of high school, during a time of 12 hours / class in each class. Problem solving and experimentation strategies were employed to foster reading, research and the collective construction of knowledge. Qualitative research was used, the data were produced by reflections in logbook, reading reports and transcription of audio recordings of the classes in which the work was implemented. The analysis of the results was performed according to the Bardin Content Analysis methodology. The data obtained indicated that several deficiencies render traditional experimental teaching inefficient and that Problem Solving can contribute to the structuring of practical activities. These activities enhance the interactivity of students, putting into practice cognitive skills (problem structuring, building strategies to solve problems, extrapolation of situations, etc.), meta-cognitive and social (group work, scientific enculturation, etc.).